Elongation improvement of transparent and flexible surface protective coating using polydimethylsiloxane-anchored epoxy-functionalized siloxane hybrid composite for reliable out-foldable displays. (15th November 2021) - Lee, Hyunhwan; Lee, Yung; Lee, Sun Woo; Kang, Seung-Mo; Kim, Yun Hyeok; Jo, Woosung; Kim, Taek-Soo; Jang, Junho; Bae, Byeong-Soo
Abstract: Flexible surface protective coating in out-foldable devices should possess high elongation with high surface hardness. However, the two characteristics in conventional protecting materials are mutually exclusive. Here, we report a simple and effective composite design strategy to realize high elastic, yet still hard out-foldable and transparent surface protective coating material using molecular hybridization between polydimethylsiloxane (PDMS) and epoxy-functionalized siloxane matrix (ESH) via an in situ sol-gel reaction, forming siloxane linkages. Chemically crosslinked PDMS with ESH (P-ESH) makes optical transparency and greatly improves the elongation property while retaining the surface hardness of ESH due to the flexible and long-siloxane backbone of PDMS. As a result, we obtain the high-performance surface protective coating with greatly improved elongation (2.05% of fracture strain, 60% increase of bare ESH) and high surface hardness (pencil hardness: 4H @ 20 μm thickness). We thoroughly characterize the mechanical behavior of P-ESH combined with microscopic (nano-scratch and nanoindentation tests) and macroscopic views (tensile test with digital image correlation methods). Enhanced elongation property with high surface hardness is induced by fully-recovery characteristics of P-ESH from external force. In addition, the fabricated P-ESH shows excellent reliability under repeated out-folding (5 mm of folding radius), continuous abrasion (steel wool test: 5, 000 cycles), acid or base solutions, and ultraviolet irradiation. Our extensible transparent surface protective coating composite provides a great potential for application to next-generation out-foldable devices.